Polymorphisms in PRKCDBP, a Transcriptional Target of TNF-α, Are Associated With Inflammatory Bowel Disease in Korean - Kim, Jung-Wook (Intest Res, 2015)
BACKGROUND/AIMS: Emerging data indicate that polymorphic sequence variations in the tumor necrosis factor alpha (TNF-α) gene may affect its production, and be associated with the risk of inflammatory bowel disease (IBD). PRKCDBP is a putative tumor suppressor gene and a transcriptional target of TNF-α. The aim of this case-control study is to explore the possible association of single nucleotide polymorphisms (SNPs) in PRKCDBP with the development of IBD in Koreans. METHODS: Genotyping analysis of four SNPs of PRKCDBP [rs35301211 (G210A), rs11544766 (G237C), rs12294600 (C797T), and rs1051992 (T507C)] was performed on 170 ulcerative colitis (UC),131 Crohn's disease (CD) patients, and 100 unrelated healthy controls using polymerase chain reaction and restriction fragment length polymorphism. RESULTS: Heterozygous configuration of three SNPs (G210A, G237C, and C797T) was very rare in both patients and healthy controls. However, allele frequencies of the T507C SNP showed a significant difference between UC patients and controls (P=0.037). The CC genotype of the T507C SNP was identified in 46.6% (61 of 131) of CD and 49.4% (84 of 170) of UC patients, but only in 33.0% (33 of 100) of healthy controls. Furthermore, CC homozygosity was more prevalent than TC heterozygosity in both CD and UC patients versus controls (P=0.016; gender-adjusted odds ratio [aOR], 2.16; 95% confidence interval [CI], 1.16-4.04 and P=0.009; aOR, 2.09; 95% CI, 1.193.64; respectively) CONCLUSIONS: Our results suggest that the T507C SNP in PRKCDBP, a TNF-α-inducible gene, might be associated with susceptibility to IBD (particularly UC) development in Koreans.